Readiness of Interprofessional Education on Maternal Health of Medical and Dental Students: A Mixed-Methods Study - Faizin, Chamim; Fahreza, Erwin Ulinnuha (Universitas Gadjah Mada, 2024)
Background: The high mortality rate and various health problems for maternal are of great concern in Indonesia. Oral and dental health of maternal receives less attention from both patients and health workers. The need for collaborative practices between doctors and dentists to optimize the health care of maternal. Interprofessional education is prepared to form medical and dental practitioners who are ready to interprofessional collaboration practice. Therefore, careful preparation is needed so that the learning process goes well and produces the desired results.This study aims to analyze the readiness of interprofessional education on maternal health among medical and dental students.Methods: This study was used mix methods. The cross-sectional quantitative method uses the questionnaire of readiness interprofessional learning scale (RIPLS) which has been modified and validated by Tyastuti (2014), containing 3 sub-scales. The qualitative method uses case studies with focus group discussions of student representatives.Results: There were 139 medical students and 49 dentistry students, both of whom had good readiness respectively 65,51 and 66,45 with a p value of 0,175. There was no significant difference in IPE readiness between the two. Good IPE readiness shows the development of teamwork, a good impression of IPE. However, there are problems that must be corrected such as bad attitudes and perceptions as well as problems in the field during home visits.Conclusion: Medical students and dental students have good readiness for maternal health of IPE, proven to give a good impression and establish teamwork. However, it still needs improvement to be even better.